Peppermint essential oil nanoliposomes: Innovative formulation for effective hair growth - Arman Suryani, Lutfi Chabib, Annisa Fitria, Siti Nurlina, Erza Ridha Kartika (Journal of Applied Pharmaceutical Science, 2025)
Peppermint essential oil is known to have properties that can stimulate hair growth by increasing blood circulation to the scalp and providing a soothing, cooling effect. However, the challenge is optimizing the delivery of these active ingredients to be more effective and safe. Therefore, the need to develop formulation modifications with the aim of drug delivery systems and nanoliposomes became the main objective of this study, which was to assess characterization, safety, and hair growth activity. Nanoliposomes were produced from a combination of Phospolipon® 80H and Phytosolve® lipoids using a thin-film hydration method. Ultrasonic dispersion and mini-extrusion methods were used to reduce the particle size. Nanoliposomes were evaluated descriptively and statistically for physical characteristics, irritation test, and hair growth effectiveness using Sprague Dawley male white rats as subjects. The nanoliposome particle size was 96.7 ± 1.9 nm, the polydispersity index (PdI) value was 0.4 ± 0.02 PdI, and the zeta potential value was −12.6 ± 0.5 mV with a round spherical shape without aggregation, milky yellow, thick with a distinctive peppermint aroma, and good homogeneity. The nanoliposome gel has met the accepted requirements through pH, viscosity, spreadability, adhesiveness, and microbial contamination limit tests. In the irritation test, all treatment groups showed no erythema and edema on the rat skin. Peppermint nanoliposome gel increased hair growth better than the other groups. Peppermint essential oil can be formulated into nanoliposome gel serum preparation and has good hair growth activity.
Keywords: Peppermint, nanoliposomes, thin layer hydration, physical characteristics, hair growth